FAKTOR-FAKTOR YANG MEMENGARUHI KEPUASAN KERJA KARYAWAN KLINIK KESEHATAN DI KOTA BEKASI - Amanda Setiorini; Wiwik Rachmarwi (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2020)
This study aims to find out whether factors such as compensation, job certainty, career path, communication, relationships with superiors, and work-life balance affect job satisfaction in three health clinics. In this research is descriptive quantitative. The results show that compensation, job certainty, communication, and work-life balance affect job satisfaction. Data processing is performed using multiple regression methods